2019
DOI: 10.1111/ijlh.13095
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of reference intervals for complete blood count parameters in venous blood for children in the Xiamen area, China

Abstract: Objectives To observe changes in the complete blood count (CBC) venous blood parameters of healthy children and establish appropriate reference intervals (RIs). Methods Overall, 4066 healthy children were selected and divided into four groups: infants, toddlers, preschool‐age children and school‐age children. Venous blood was analysed for 17 parameters. Outlier data for each parameter were eliminated and RIs were established based on the Clinical and Laboratory Standards Institute C28‐A3c guideline. Results Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
5
10
0
Order By: Relevance
“…Those findings are in accordance with the previous reports [9,25]. We also found a decrease of WBC levels as age increases, which is in line with previous studies [7,26]. In brief, we noticed few differences between females and males of 6-10 years of age, in fact, only 7 out of 18 parameters were significant.…”
Section: Discussionsupporting
confidence: 93%
“…Those findings are in accordance with the previous reports [9,25]. We also found a decrease of WBC levels as age increases, which is in line with previous studies [7,26]. In brief, we noticed few differences between females and males of 6-10 years of age, in fact, only 7 out of 18 parameters were significant.…”
Section: Discussionsupporting
confidence: 93%
“…The identified RIs of main parameters including RBC, Hb, HCT, WBC, and PLT were compared with 3 published venous RIs, including 2 studies from China and 1 study from Canada. 5,7,16 The interval for RBC count, Hb, HCT in children increased with age in the present study and this trend is consistent with these 3 reports. The upper and lower limits of RBC count, Hb, HCT in each group in the present study were close to those established in China, especially in ShunYi, which is one district of Beijing, and slightly higher than those established in Canada.…”
Section: Discussionsupporting
confidence: 93%
“…As in other studies, males exhibited a slightly higher MONO#, compared with females; in contrast, females exhibited a slightly higher concentration than males for WBC during puberty. [ 7 , 12 ] (2) LYMPH# [Figure 2 B] was low during infancy and increased to its highest level at 6 months of age; then, the 50th and 97.5th quantiles of LYMPH# exhibited moderate and continuous reduction until approximately 9 years of age. In addition, LYMPH# appeared slightly higher in males than in females during puberty.…”
Section: Resultsmentioning
confidence: 99%
“…The present study demonstrated dramatic changes in both total and differential WBCs throughout childhood, especially in the early stages of life, which was consistent with previous research. [ 7 , 12 ] Also, LYMPH# and NEUT# exhibited more obvious age-dependent changes during childhood, compared with EO#, BASO#, and MONO#. As shown in Figure 2 B, LYMPH# exhibited its lowest level during infancy and increased to its highest level at 6 months of age, then exhibited moderate and continuous reduction until approximately 9 years of age; these patterns reflect the changes in children's exposure to foreign antigens with increasing age, [ 19 ] and are consistent with the overall timing of pediatric diseases.…”
Section: Discussionmentioning
confidence: 99%